A smart enzyme reactor based on a photo-responsive hydrogel for purifying water from phenol contaminated sources. Issue 4 (24th December 2021) - Gu, Yuqi; Luo, Siyuan; Wang, Yaya; Zhu, Xuhui; Yang, Shun
Abstract : In this paper, a smart enzyme reactor (SER) was synthesized using immobilized tyrosinase (Tyr) in a photo-responsive hydrogel via a polydopamine-assisted self-assembly strategy for purifying water from phenol contaminated water. Abstract : In this paper, a smart enzyme reactor (SER) was synthesized using immobilized tyrosinase (Tyr) in a photo-responsive hydrogel via a polydopamine-assisted self-assembly strategy for purifying water from phenol contaminated water. PDA was not only utilized as a binder between Tyr and the hydrogel to prevent the leakage of Tyr with relatively high enzymatic activity from the SER, but also acted as a light absorber to trigger the hydrophilic/hydrophobic switching of PNIPAm hydrogels to realize the efficient reclamation of clean water. Experimental results showed that the SER maintained a well-defined porous structure with excellent elasticity, which was beneficial for water transport and enzyme accessibility. And the stability and reusability of Tyr in the degradation of phenol were all improved. Furthermore, clean water could be reclaimed completely and facilely by light irradiation after enzymatic remediation in the SER.